DISTINCTIVE GENETIC FEATURES OF K-RICH BASITES - Zolotukhin V.V.; Vasil'ev Yu.R. (My University, 2002)
The genesis of K-rich basites is discussed on the basis of the authors' materials on high-K basalts from the northern Siberian Platform and data compiled from the literature on other areas worldwide. The petrology, geochemistry, and mineralogy of the rocks are considered along with their relations with other accompanying volcanic rocks and with their specific geodynamic features in island-arc, continental margin, and continental rift environments. It is demonstrated that K-basalts and related high-K rocks are produced by a combination of two processes: (1) crystallization differentiation of intruded mantle subalkaline basaltic melts and (2) their enrichment in K and associated incompatible elements during the inflow of fluids rich in these elements along subvertical rift zones. The genesis of K-rich mafic magmas supposedly included an earlier stage, which involved mantle metasomatism in the source (that graded into potassic magmometasomatism of the first partial melts) and a later "metamagmatic" stage with the participation of potassic metasomatism. An important factor in the genesis of high-K basites was the apparent inflow of K into the parental magma, whereas hybridism (a process commonly proposed to account for the genesis of these rocks) was most probably potassic magmometasomatism.